Histogram Analysis of Apparent Diffusion Coefficient in Differentiating Pancreatic Adenocarcinoma and Neuroendocrine Tumor. Issue 4 (January 2016) - Shindo, Toshikazu; Fukukura, Yoshihiko; Umanodan, Tomokazu; Takumi, Koji; Hakamada, Hiroto; Nakajo, Masanori; Umanodan, Aya; Ideue, Junichi; Kamimura, Kiyohisa; Yoshiura, Takashi
Abstract : Abstract: The aim of this study was to investigate whether histogram analysis in diffusion-weighted (DW) magnetic resonance imaging (MRI) can help differentiate pancreatic adenocarcinomas from neuroendocrine tumors. Sixty-four patients with histologically confirmed 53 pancreatic adenocarcinomas or 19 neuroendocrine tumors underwent DW MRI. We evaluated the pixel distribution histogram parameters (mean, skewness, kurtosis, and entropy) of the apparent diffusion coefficient (ADC) values derived from b -values of 0 and 200 (ADC200 ), 0 and 400 (ADC400 ), or 0 and 800 (ADC800 ) s/mm 2 . Histogram parameters were compared between pancreatic adenocarcinomas and neuroendocrine tumors, and the diagnostic performance was evaluated by using receiver operating characteristic (ROC) analysis. The mean ADC200 and ADC400 were significantly higher in neuroendocrine tumors than in pancreatic adenocarcinomas ( P  = 0.001 and P  = 0.019, respectively). Pancreatic adenocarcinomas showed significantly higher skewness and kurtosis on ADC400 ( P  = 0.007 and P  = 0.001, respectively) and ADC800 ( P  = 0.001 and P  = 0.001, respectively). With all b -value combinations, the entropy of ADC values was significantly higher in pancreatic adenocarcinomas ( P  < 0.001 for ADC200 ; P  = 0.001 for ADC400 ; P  < 0.001 for ADC800 ), and showed the highest area under the ROC curve for diagnosing adenocarcinomas (0.77 for ADC200, 0.76 for ADC400, and 0.78 for ADC800 ). ADC histogram analysis of DW MRI can help differentiate pancreatic adenocarcinomas from neuroendocrine tumors.